Design Layout and Circulation Design of Type A Passenger Terminal in Kota Singkawang - Adna, Serafina Gebria; Said, Said; Mukti, Elsa Tri (Jurnal Teknik Sipil, 2024)
Kota Singkawang, located in Kalimantan Barat Province, is a popular destination for domestic and international visitors. According to the 2013"“2032 Regional Spatial Plan (RTRW), a Type A passenger terminal is planned on Jl. Terminal Induk, Kota Singkawang. However, the terminal's construction is still pending, and the Singkawang Grand Mall currently serves as a temporary terminal for the new Singkawang-Malaysia bus route, which began operations on December 1, 2023. Our research, involving experts from various fields, focuses on designing the Kota Singkawang Type A passenger terminal layout based on necessary facilities and circulation needs. The terminal requires a minimum of 4.7 hectares, but only 2.42 hectares are available. The design accommodates separate circulations for buses and passengers, with specific parking spaces for various transport modes. Given the shortage of 2.28 hectares, an expansion of the terminal's land is recommended. Additionally, it is suggested that Jl. Terminal Induk will be upgraded to a primary arterial road with a minimum width of 11 meters to support future development.Keywords: Transportation Development, Passenger Terminals, Multimodal Connectivity, Cross-Border Transportation, Regulatory Standards